2013
DOI: 10.1515/jms-2016-0184
|View full text |Cite
|
Sign up to set email alerts
|

Non-State Actors in Cyberspace Operations

Abstract: The growing importance of cyberspace to modern society, and its increasing use as an arena for dispute, is becoming a national security concern for governments and armed forces globally. The special characteristics of cyberspace, such as its asymmetric nature, the lack of attribution, the low cost of entry, the legal ambiguity, and its role as an efficient medium for protest, crime, espionage and military aggression, makes it an attractive domain for nation-states as well as non-state actors in cyber conflict.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 20 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…Increasing the size of the early flatter region corresponds to a greater barrier to entry, and our model correctly predicts long-term stable hegemony in this case. Finally, reducing the size of the region (a smaller exponent) means lowering the barriers to entry, for example, in cyberspace, where although the power of a nation state is not easy to come by, small actors can nonetheless have a large impact [27], and our model predicts much greater instability in this power-diffuse domain, in line with the expectations of some scholars [28].…”
Section: Discussionsupporting
confidence: 85%
“…Increasing the size of the early flatter region corresponds to a greater barrier to entry, and our model correctly predicts long-term stable hegemony in this case. Finally, reducing the size of the region (a smaller exponent) means lowering the barriers to entry, for example, in cyberspace, where although the power of a nation state is not easy to come by, small actors can nonetheless have a large impact [27], and our model predicts much greater instability in this power-diffuse domain, in line with the expectations of some scholars [28].…”
Section: Discussionsupporting
confidence: 85%
“…Network warfare is quite close to cyber warfare. Cyber warfare includes cyber penetration, cyber manipulation and cyber robbery (Sigholm, 2013, p. 51, Lehto et al, 2017. Conley et al (2016) state that Non-physical Network Defence is defence against security, business, intelligence, political, contact and company networks that are guided, owned and funded by a foreign state, as well as opaque foreign state networks.…”
Section: Related Researchmentioning
confidence: 99%
“…Although previous studies (Lehto et al, 2017, Nimmo, 2015, Pomerantsev, 2015, Sigholm, 2013, p. 51, Mäntylä, 2014, Joint Chiefs of Staff, 2013, Armistead et al, 2004pp. 13-20, Schechtman, 1996 have shown that a great deal of components of defence strategies exist in societies' IE, qualitative research of the origins of components of defence strategies and how a society becomes aware of these is lacking.…”
Section: Introductionmentioning
confidence: 96%
“…Examples of state threat actors are militaries, foreign intelligence services and state-sponsored hackers. Non-state threat actors include hacktivists, terrorists and jihadists, who often operate beyond legal jurisdictions [24]. Table 3 provides a comparative analysis of the associated geopolitical risk arising from related IoT threat incidents.…”
Section: B Geopolitical Issues and Adversariesmentioning
confidence: 99%